Differences in N2O Fluxes and Denitrification Gene Abundance in the Wet and Dry Seasons Through Soil and Plant Residue Characteristics of Tropical Tree Crops - Nishisaka, Caroline Sayuri; Youngerman, Connor; Meredith, Laura K.; do Carmo, Janaina Braga; Navarrete, Acacio Aparecido (Frontiers in Environmental Science, 2019)
The conversion of forest to agricultural soils is a widespread activity in tropical systems, and its link to nitrous oxide (N2O) fluxes and nitrogen cycling gene abundance is relevant to understand environmental drivers that may interact with climate change. A current challenge to estimating N2O emissions from land use conversion is an incomplete understanding of crop-specific impacts on denitrifier communities and the N2O fluxes driven by differences in the above- and below-ground inputs with crop type. To address this knowledge gap in tree crops, we evaluated N2O fluxes and denitrification gene abundance and their relationships with soil and plant residue characteristics in citrus and eucalyptus plantations in the field and in soil incubations. We found that the accumulated N2O fluxes from soil were lower for the two agricultural field sites than those for their adjacent forest sites in dry and wet seasons. The N2O fluxes were higher in the wet season, and this seasonal difference persisted even when the soils collected from both seasons were incubated under the same moisture and temperature conditions in the lab for 30 days. Increased N2O fluxes in the wet season were accompanied by an increase in soil nirK and nosZ gene abundance, the dissolved organic carbon (DOC) concentration, and the total soil carbon (C) and nitrogen (N) content. In turn, the abundance of denitrifiers, as indicated by nirK, nirS and nosZ gene copy numbers, showed a low but significant positive correlation with soil bulk density. Our results suggest that soil moisture, leaf litter and crop residues influence the seasonal differences in both N2O fluxes and abundance of denitrifiers in citrus- and eucalyptus-cultivated soils, likely through effects on soil physicochemical characteristics. These findings highlight the overwhelming role of environmental drivers that can make investigating microbial drivers difficult in the field and open the possibility for a better understanding of N cycling processes in tropical soils based on paired field- and incubation-based experimentation.